(untitled) (Balthazar, 2024)
In this essay, we focus mainly on Intervista (1987), a film set on the set of a film based on Kafka’s Amerika. Here Fellini seems to identify himself with Kafka, not for the purpose of portraying the Prague writer’s novel, deemed already «too visual», but on the contrary to talk about himself, about his own sentimental upbringing during his adolescence and his own way of filmmaking. The game of mirroring is complex and does not stop at the autobiographical level: it allows us to grasp the meaning of Fellini’s cinema, which is to grasp reality through the imagination, as Milan Kundera wrote. If we focus on the late Fellini, we can say that cinema is image and words are superfluous. Words tell, while the image shows. Words are tied to ideologies, to grand narratives, while the image is as free as the language of dreams, which Fellini is inspired by referring to Jung. Therefore, the Fellini film image is by no means a verisimilar representation; rather, it is a meta-image that uses kafkaesque poetics to speaks, with ironic levity, about the fate of cinema in the modern world, in which nightmare blends with reality, as the unfinished project Il viaggio di G. Mastorna shows.